O íntimo na fotografia contemporânea : a narrativa no processo criativo fotográfico - Soares, Nícolas Oliveira (2015)
The dissertation focuses on the intimate aspects as manifestation in contemporary photographic production. It is intended an outline of the self -intimate, everyday, páthos; and even the aesthetic artifice of the very photography, within its technical and